Spectroelectrochemical characterization and controlled potential chronocoulometric demetallation of tetra- and octa-substituted lead phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
The solution redox properties and spectroelectrochemical investigation of the novel lead phthalocyanines carrying chloro alkylthio and alkyl-malonyl at periphery were studied using various electrochemical techniques in DCM on a platinum electrode. Cyclic voltammetry and differential pulse voltammetry studies show that all of the complexes give up to five ligand-based diffusion controlled one-electron reversible redox couples. Assignments of the redox couples were confirmed by spectroelectrochernical measurements. Spectroelectrochemical studies reveal that lead phthalocyanine complexes are demetallated during the controlled potential chronocoulometry measurement before the first reduction couple of the complexes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; lead; demetallation; cyclic voltammetry; spectroelectrochemistry; METAL-FREE; ELECTROCHEMISTRY; REDUCTION; BEHAVIOR; COBALT